Similarities and differences in well-being between Australian, Saudi Arabian and South African pre-registration nursing students. Issue 4 (August 2020) - Fernandez, Ritin; Ham-Baloyi, Wilma ten; Al Mutair, Abbas; Lapkin, Sam; Moxham, Lorna; Tapsell, Amy
Abstract: Background: Emotional wellbeing is essential for mental and physical health. Although all university students are vulnerable to psychological distress, nursing students are particularly susceptible, and recognised at higher risk due to the stressful nature of the nursing program. Aim: The aim of this cross-sectional study was to compare the demographic characteristics and emotional wellbeing with regard to levels of anxiety, depression, behavioural control, positive affect and general distress of preregistration nursing students in Australia, Saudi Arabia and South Africa. Design: Cross-sectional design. Methods: A total of 1381 pre-registration nursing students from two universities in Saudi Arabia and one university in both Australia and South Africa completed the self-report measurement tool, the Mental Health Inventory. A one-way analysis of variance was used to compare well-being among pre-registration nursing students in these three countries. Findings: The results revealed that when compared to the Australian and South African cohorts, the Saudi Arabian cohort had significantly higher anxiety (Australia M  = 26.79, SD =  8.15; Saudi Arabia M  = 33.12, SD  = 8.24; South Africa M  = 29.48, SD  = 7.54), depression, (Australia M  = 10.15, SD  = 3.65; Saudi Arabia M  = 13.10, SD  = 4.49; South Africa M  = 11.83, SD  = 3.72), and lower scores in the Mental Health Inventory (Australia M  = 152.44, SD  = 28.60; Saudi Arabia M  = 138.11, SD  = 30.09; South Africa M  = 145.67, SD  = 26.32). Conclusion: There were statistically significant differences in overall psychological distress and well-being among students in the three countries. Strategies to improve emotional wellbeing and reduce the negative aspects of mental health such as anxiety and depression of preregistration nursing students are needed.